Strategies for facilitating inclusive campuses in higher education : international perspectives on equity and inclusion - Hoffman, Jaimie; Blessinger, Patrick; Makhanya, Mandla (Innovations in higher education teaching and learning, 2019)
Higher education institutions continue to encounter an increasingly complex set of issues regarding equity, diversity and inclusion on university campuses. Many institutions are striving to find creative solutions to eliminate access, participation, and achievement barriers as well as practices that impede retention and graduation rates. This volume provides educators with a global understanding of the successes and challenges associated with facilitating inclusive campuses in higher education amidst the growing diversity of students by providing evidence-based strategies and ideas for implementing equity and inclusion at higher education institutions around the world.By addressing challenges experienced at a cross-cultural level, this book is an invaluable resource for educators and higher education practitioners alike.